Abrupt Intensification and Dissipation of Tropical Cyclones in Indian Ocean: A Case Study of Tropical Cyclone Nilofar – 2014 - Abdul Qayoom Bhutto; Muhammad Jawed Iqbal; Mirza Jawwad Baig (Journal of Basic & Applied Sciences, 2017)
This study aims to investigate the possible influence of different atmospheric forcing on intensification/dissipation of tropical cyclonic “Nilofar” in Arabian Sea appeared during the last week of October, 2014 which exhibited abrupt intensification and dissipation as well. The cyclone was monitored by the Tropical Cyclone Warning Center (TCWC) of Pakistan Meteorological | department and the Regional Specialized Meteorological Center (RSMC) of Indian Meteorological | department (IMD) continuously, issued warnings and advisories with the help of available synoptic observations, satellite data and numerical models. Almost all the essential ingredients for intensification and tracking of the cyclone were studied and monitored accurately. Although the track forecast of the cyclone remained up to mark; but great errors occurred in intensity forecast. The atmospheric vertical wind shear could not be studied accurately. The intensity of wind shear itself is dependent on both; the local and global atmospheric forcing and climate variables, reoccurring periodically, especially while occurring two or more at the same time. More studies are required for influence of these climate variables while co-occurring at the same time period. This study will help weather forecasters to pay special attention on variation of climate factors affecting the wind shear for proper forecasting of tropical cyclones in the Arabian Sea for the safety of coastal communities along the coast.